Fabrication and characterisation of hydrophobic magnetite composite nanoparticles for oil/water separation. (2nd January 2016) - Pei, Y.; Han, Q.; Tang, L.; Zhao, L.; Wu, L.
Abstract : The hydrophobic Fe3 O4 composite nanoparticles were synthesised for oil/water separation in a simple and relatively inexpensive way. First, the Fe3 O4 nanoparticles were prepared through chemical coprecipitation and then were coated SiO2 layer via sol–gel method. Subsequently, the obtained Fe3 O4 @SiO2 nanoparticles were modified with methacryloxypropyltrimethoxysilane (MPS); thus, the methacryloxypropyl group was grafted onto the surface of Fe3 O4 @SiO2 through condensation reaction of hydroxyl groups of SiO2 shell and MPS molecules after hydrolysis. Fourier transformer infrared, X-ray diffraction (XRD), vibrating sample magnetometer and contact angle (CA) measurement were used to characterise the microstructure, magnetic property and surface property of Fe3 O4 @SiO2 –MPS nanoparticles. The measurement results revealed that Fe3 O4 @SiO2 –MPS nanoparticles exhibited excellent hydrophobicity with CA of water 137 ± 3°, and CA of oil nearly 0°, as well as intense superparamagnetism with saturation magnetisation of 44·24 emu g − 1 . The Fe3 O4 @SiO2 –MPS nanoparticles had found application in oil/water separation by applying an external magnetic field due to their hydrophobic and magnetic property. Furthermore, the Fe3 O4 @SiO2 –MPS nanoparticles could be recovered after washing and filtration, and the oil absorption ability only decreased slightly. These hydrophobic superparamagnetic composite nanoparticles could find application in separation and concentration areas due to their unique hydrophobicity and magnetic responsiveness.